2013
DOI: 10.1186/1472-6874-13-13
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive rights and options available to women infected with HIV in Ghana: perspectives of service providers from three Ghanaian health facilities

Abstract: BackgroundOwing to improved management of HIV and its associated opportunistic infections, many HIV-positive persons of reproductive age are choosing to exercise their right of parenthood. This study explored the knowledge of health workers from two Ghanaian districts on the reproductive rights and options available to HIV-positive women who wish to conceive.MethodsFacility-based cross-sectional in design, the study involved the entire population of nurse counselors (32) and medical officers (3) who provide co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
(18 reference statements)
2
5
1
6
Order By: Relevance
“…Health care providers in our focus groups were ambivalent about HIV-infected individuals having children. This has also been reported in Cape Town [ 5 ] and Ghana [ 19 ]. Providers believe in reproductive choices and recognize that they cannot make these decisions for their clients.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Health care providers in our focus groups were ambivalent about HIV-infected individuals having children. This has also been reported in Cape Town [ 5 ] and Ghana [ 19 ]. Providers believe in reproductive choices and recognize that they cannot make these decisions for their clients.…”
Section: Discussionsupporting
confidence: 79%
“…Certain service providers expressed an undertone of judgment related to people with HIV desiring children. Studies in Cape Town [ 15 ], Argentina [ 20 ], Nigeria [ 21 , 22 ] and Ghana [ 19 ] show that fertility choice among people with HIV is often not possible in a climate of judgmental and/or overtly negative attitudes of healthcare providers. In our previous study on fertility desires and intentions from these same two clinics, clients revealed the importance of provider authority and opinion in their decisions about childbearing [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were also fears that previous corrupt officials linked to the National Social Security Fund (NSSF) and National Health Insurance Fund (NHIF) would manipulate the new scheme for their gain [ 5 ]. The degree to which knowledge influences utilisation, acceptability and smooth implementation of health care interventions has been investigated previously [ 6 8 ]. Implementing a new system is no exception to the above.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, among a sample of university students in Lebanon, formal healthcare seeking behavior for psychological concerns was exceedingly low at 3% (El Kahi, Abi Rizk, Hlais, & Adib, 2012). Additionally, women in the Middle East may tend to delay seeking formal healthcare and instead opt for self-prescribed medications and home treatments due to gendered socio-cultural roles, financial concerns, and perceptions about quality of care and health needs (Majaj, Nassar, & De Allergi, 2013). Women in the region may also prioritize seeking healthcare for physical symptoms over psychological symptoms (Kabakian-Khasholian, Shayboub, & Ataya, 2014).…”
Section: Discussionmentioning
confidence: 99%